Intracoronary polarimetry for characterizing coronary plaque vulnerability in patients with coronary artery disease. (25th November 2020) - Otsuka, K; Villiger, M; Van Zandvoort, L.J.C; Neleman, T; Karanasos, A; Dijikstra, J; Van Soest, G; Regar, E; Nadkarni, S.K; Daemen, J; Bouma, B.E
Abstract: Background: Intracoronary polarimetry with polarization-sensitive (PS-) optical frequency domain imaging (OFDI) measures polarization properties, including birefringence and depolarization, in parallel with structural features of conventional OFDI (Figure 1A). Collagen, which imparts mechanical integrity to fibrous caps, and collagen-synthesizing smooth muscle cells exhibit elevated birefringence. Depolarization is increased by the presence of macrophages and lipid/necrotic cores. Purpose: This study aimed to compare conventional OFDI and polarimetric signatures of coronary lesions between patients with acute coronary syndrome (ACS) and chronic coronary syndrome (CCS). Furthermore, we aimed to determine a birefringence cut-off value for identifying which fibrous caps belong to ACS culprit lesions. Methods: This study consisted of 37 patients with ACS (n=23) or CCS (n=14). ACS culprit lesions (ACS-lesions) and CCS stenotic lesions (CCS-lesions) were included in the analysis (820 mm). Qualitative and quantitative conventional OFDI analysis included the presence of plaque rupture, macrophage infiltration, micro-vessels, thrombus, stenosis severity, fibrous cap thickness (FCT), lipid arc, lipid-burden and calcium-burden index. Birefringence and depolarization of the coronary lesions and fibrous caps were measured in the cross-sectional images showing the minimum FCT or minimum luminal area. Predictors of ACS-lesions were investigated by multivariate regression analysis. Receiver operating characteristic (ROC) analysis was used to determine the birefringence cut-off value identifying ACS fibrous caps (ACS-caps). Results: There were no significant differences in clinical characteristics between the two groups, except for previous history of coronary artery disease. Compared to CCS-lesions, ACS-lesions featured higher lipid-burden index and maximum lipid arc (both p<0.05). ACS-lesions featured lower birefringence and higher depolarization than CCS-lesions (p<0.05). Multivariable regression demonstrated an independent association of birefringence with ACS-lesions (p<0.05), even after adjusting for the conventional OFDI findings. Limiting the analysis to the fibrous caps, ACS-caps exhibited significantly lower birefringence (p<0.05) and higher depolarization (p<0.05) that CCS-caps. ROC analysis for differentiating ACS-caps from CCS-caps found that a birefringence value of 0.0004 results in a sensitivity and specificity of 88% and 82%, respectively (Figure 1B, AUC = 0.82). Conclusions: Intracoronary polarimetry provides quantitative assessment of coronary lesions related to their composition. Birefringence was an independent robust predictor of ACS-lesions. Decreased birefringence and pronounced depolarization within the ACS-caps may indicate increased collagenolytic activity and macrophage infiltration, respectively. These results suggest that polarization properties may serve as quantitative imaging markers for assessing plaque vulnerability. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): This work was supported by the National Institutes of Health and by Terumo Corporation.